BEYOND CENTERS AND CIRCLE TIME LEARNING IN EARLY CHILDHOOD (CASE OF RAUDHATUL ATHFAL) IN PAREPARE CITY - Djollong, A. Fitriani; Juhannis, Hamdan; Saat, Sulaiman; Maulana, Andi (Jurnal Diskursus Islam, 2021)
This article aimed to describe and evaluate the implementation of beyond centers and circle time learning in early childhood at Raudhatul Athfal in Parepare city. This study employed qualitative research with a phenomenological approach to observe and be directly involved in implementing Beyond Centers and Circle Time learning in early childhood at Raudhatul Athfal in Parepare City. The objects of this study were from Raudhatul Athfal UMDI Al Ihsan and at Raudhatul Athfal UMDI Ujung Baru Parepare City. The data collection methods used were observation, interviews, documentation, and triangulation. The validity testing of the data was carried out, namely internal validity, external validity and reliability. The study results indicate that the learning of beyond centers and circle time is one of the lessons aimed to meet the children’s needs; it is carried out by serving the fun play to stimulate children’s creativity and innovation with the support of the environment the learning process. This learning method is used to develop the children’s life skills by using a footing that is implemented gradually and repeatedly so that the aspects of the children’s development gain a comprehensive stimulus covering all aspects of development. Learning beyond centers and circle time is based on the growth and ability of the children, which aimed to form and develop an exploratory trait, shape and develop a creative trait, as well as form and develop an integral personality as outlined through directed, planned and fun play activities based on the tasks of child development according to the children’s developmental stage.